Performing Emil Hartmann "“ The Importance of Musical Contextualisation: A practice-based research project - Robertson, Garreth Damon (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
When embarking on a journey of preparing a musical work for performance, a contextualisation process is undertaken which informs the performer/s of the factors which govern the parameters of the work. In this study, the author performed Emil Hartmann's piano trio op. 10 as a part of an integrated master's degree program. As the composer was not a part of mainland European musical society, information on his life and work was difficult to access, which presented the performer with a contextualisation problem. This study aimed to highlight the process of contextualisation, in the absence of sufficient literary material, through the lens of Emil Hartmann's piano trio op. 10. The research used a three-pronged methodological approach in order to construct the narrative around Hartmann's life and composition. Through a structured process of using practice-based research to analyse the creative process undertaken by the practitioners, alongside a micro-historical and analytical methodology, the study builds layers of understanding to inform Hartmann's narrative, and thus provides interpretational insight into the execution of the work. The research finds that, although it is possible to interpret a musical work based on the musical score, there are layers of depth which cannot be accessed without a contextual understanding of the composer and the conditions in which the composition was written. Through forming the narrative on Emil Hartmann and his piano trio, the research uses the methodology to highlight a method which can be undertaken in the absence of contextual knowledge, and thus presents a contextual understanding of Emil Hartmann's narrative. With the constructed knowledge, the author uses the findings based on the methodological approaches to weave a narrative around the life of Emil Hartmann. Applying the information discovered in the findings, interpretational approaches are discussed to inform future performances of the work.
Keywords: Hartmann, Emil, 1836-1898; Hartmann, Emil, 1836-1898 -- Criticism and interpretation -- History -- 19th century; Practice (Philosophy); Research -- Methodology; Contextualism (Philosophy); Music -- Denmark -- History and criticism; Music appreciation; Musical analysis